The Concept of Islamic Education in The Perspective of Hasan Langgulung and its Relevance in the Era of Globalization - Ainussofa, Lamik; Haryanto, Budi (Al-Fikru: Jurnal Ilmiah, 2024)
Islamic education in the era of globalization faces great challenges in maintaining moral and spiritual values in the midst of modernization. A poorly adaptive curriculum and a lack of integration of Islamic knowledge and values are the main problems. This study examines Hasan Langgulung's thoughts on Islamic education and its relevance in facing globalization. Using library methods, various works by Langgulung and writings discussing his thoughts were analyzed in depth. The results showed that Langgulung's ideas were not only oriented towards Islamic-based education, but also emphasized the development of a dynamic curriculum, the integration of science with Islamic teachings, and a comprehensive evaluation of education. His thinking emphasizes that Islamic education must be able to produce individuals who are intellectually intelligent, have strong character, and have high religious awareness. The implications of this research show that Langgulung's thinking can be a reference in designing an Islamic education system that is more adaptive to globalization. Therefore, further study is needed to develop an implementation strategy that suits the needs of Islamic education in Indonesia.